Isolation of Seed-Borne Fungi of Wheat and Their Control Using Aqueous Plant Extract of Ageratum houstonianum Mill - Chhetri , Roshan (Dhaulagiri Journal of Contemporary Issues, 2026)
Seed-borne fungi are important constraints in wheat production and storage because they reduce seed quality, germination, and crop productivity. Plant-based extracts are increasingly considered eco-friendly alternatives to synthetic fungicides for managing seed-borne fungal pathogens. Seeds of Triticum aestivum L. were collected from three households in Kathekhola Rural Municipality-8, Gandaki Province, Nepal, and were tested for seed-borne fungi using the standard blotter technique. A total of 25 wheat seeds were examined in this laboratory-based study. On testing, five different fungi, namely Aspergillus niger, Fusarium oxysporum, Aspergillus flavus, Alternaria sp., and Alternaria alternata, were isolated, among which Aspergillus niger showed the highest incidence. However, Alternaria alternata and Fusarium oxysporum were selected for in vitro inhibition tests. The aqueous leaf extract of Ageratum houstonianum Mill. was prepared for mycelial inhibition against Alternaria alternata and Fusarium oxysporum at concentrations of 25%, 50%, and 100%. Fusarium oxysporum was completely inhibited by A. houstonianum at 100% crude extract, while Alternaria alternata was inhibited by 88.09% at the same concentration. Inhibition gradually increased from lower to higher concentrations. The extract of A. houstonianum was more effective against Fusarium oxysporum than against Alternaria alternata. The findings of this study suggest that A. houstonianum leaf extract may serve as a potential eco-friendly alternative to synthetic fungicides for managing selected seed-borne fungi in wheat. However, further studies with larger seed samples, molecular identification of fungi, and field trials are needed to validate its practical application.